Hyaluronan-induced alterations of the gut microbiome protects mice against Citrobacter rodentium infection and intestinal inflammation. (1st January 2021) - Mao, Tangyou; Su, Chien-Wen; Ji, Qiaorong; Chen, Chih-Yu; Wang, Rongjun; Vijaya Kumar, Deepak; Lan, Jinggang; Jiao, Lefei; Shi, Hai Ning
ABSTRACT: Hyaluronan is a glycosaminoglycan polymer that has been shown to play an important role in homeostasis of the gastrointestinal tract. However, its mechanistic significance in gastrointestinal epithelial barrier elements remain unexplored. Here, our results revealed that hyaluronan treatment resulted in significant changes in the gut microbiota in mice. To demonstrate the functional consequences of hyaluronan-treatment and hyaluronan-induced microbiota alterations, Citrobacter rodentium- and DSS-induced colitis models and microbiota transplantation approaches were utilized. We showed that hyaluronan alleviated intestinal inflammation in both pathogen and chemically induced intestinal mucosal damage. The protection in bacterial colitis was associated with enhanced C. rodentium clearance and alleviation of pathogen-induced gut dysbiosis. Microbiota transplantation experiments showed that the hyaluronan-altered microbiota is sufficient to confer protection against C. rodentium infection. Colonization with Akkermansia muciniphila, a commensal bacterium that is greatly enriched by hyaluronan treatment, alleviated C. rodentium -induced bacterial colitis in mice. Additionally, Akkermansia -induced protection was found to be associated with the induction of goblet cells and the production of mucins and epithelial antimicrobial peptides. Collectively, these results provide novel insights into the regulatory role of hyaluronan in modulating the gut microbiota and immunity in enteric infection and inflammation, with therapeutic potential for gut microbiome-targeted immunotherapy.